2014
DOI: 10.12691/ajwr-2-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Access to Potable Water Supply in Nigerian Cities Evidence from Yenagoa Metropolis

Abstract: The importance of safe water supply to human health cannot be over emphasized. However, potable water supply to most Nigerian cities is still inadequate. This study was designed to determine households' access to potable water supply in Yenagoa, in terms of quality and quantity. To achieve this aim, 15 borehole water samples were collected from 15 neighbourhoods, which the metropolis was structured. 375 questionnaires were randomly distributed in these neighbourhoods using the systematic sampling technique. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 1 publication
2
9
1
Order By: Relevance
“…The Population Institute noted further that with a projected population of the world to expand to 9 billion people by 2050, it is estimated that 90 percent of the additional 3 billion people will be living in developing countries, many of which are already experiencing water stress or scarcity. In Calabar, the situation is dire and similar to what is obtainable in other Nigerian cities as noted by Krebs (2010), Ohwo and Abotutu (2014), Lawal and Bashorun (2015), etc. A preliminary survey by the authors in Calabar revealed that institutional and physical problems have diminished the availability of the essential commodity, forcing residents to resort to construction of boreholes in their compounds and where a borehole is not present in the residence, women, young men and children are seen spending reasonable time carrying buckets and other containers to and from other water supply sources.…”
Section: Introductionsupporting
confidence: 62%
“…The Population Institute noted further that with a projected population of the world to expand to 9 billion people by 2050, it is estimated that 90 percent of the additional 3 billion people will be living in developing countries, many of which are already experiencing water stress or scarcity. In Calabar, the situation is dire and similar to what is obtainable in other Nigerian cities as noted by Krebs (2010), Ohwo and Abotutu (2014), Lawal and Bashorun (2015), etc. A preliminary survey by the authors in Calabar revealed that institutional and physical problems have diminished the availability of the essential commodity, forcing residents to resort to construction of boreholes in their compounds and where a borehole is not present in the residence, women, young men and children are seen spending reasonable time carrying buckets and other containers to and from other water supply sources.…”
Section: Introductionsupporting
confidence: 62%
“…Over the years there has been an increase in the literature on different aspect of water provision, to avail policy makers with reliable information to take informed dicisions, which would lead to sustainable water provision by thier respective public water utilities. Some of these studies focused on access to improve sources of water supply, cost of water and quality and quantity issues (Ohwo & Abotutu, 2014; Ohwo, 2014a; Wagah, Onyango & Kibwage, 2010; Abaje, Ati & Ishaya, 2009) with few focusing on the service quality of the respective public water providers, using customer perception of selected variables to determine customers satisfaction/dissatisfaction (Kassa & Chernet, 2017;Gowela et al, 2017;Abubarka, 2016, Ojo, 2011. Some of the studies in the literature undertaken outside the study area have reported contrary results.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that increasing population has caused a serious water stress in the area and that the areas closer to the water board had more water supply than those areas that are farther away. In the same vein, [21] assessed access to potable water supply in Nigerian cities, evidenced from Yenagoa Metropolis of Bayelsa State. Their study was designed to determine households' access to potable water supply in Yenagoa, in terms of quality and quantity.…”
Section: Literature Reviewmentioning
confidence: 99%